Pengaruh Penggunaan Media Gambar Seri Terhadap Perkembangan Bahasa Anak Pada Kelompok B Di Tk Pertiwi 2 Blimbing Sambirejo Sragen Tahun Ajaran 2016/2017 - Afina, Anisa Salma, Drs. Amrul Choiri, M.Ag (2017)
The aim of this research which is to determine whether there is the influence of the use of picture series media to the development of children's language in group B at Pertiwi 2 Kindergarden of Blimbing Sambirejo Sragen in academic year 2016/2017. ". This research takes place in Pertiwi 2 ergarden of Blimbing Sambirejo Sragen which use quantitative experimental research. The population in this research are 25 children and the samples are taken every child in group B. Data collection techniques in this research is conducted through observation, which is observation participate. Data analysis techniques in this research using a t-test with SPSS 16.0 for Windows. The results of data analysis using t-test is obtained t - -ttabel ≤ 7.124 -ttabel-1.7109 so, H0 is rejected and Ha is accepted. It means that it has the influence of the use picture series media to the development of children's language.Keywords: the use of images series media, language development